ANALYSIS OF A STATUS AND INCREASE IN QUALITY OF CONDUCTING TEST OF INTERACTION PROCESS OF BRUSHES OF THE REMOVER AND SPINDLES OF THE MECHANICAL COTTON PICKER BY USING DIGITAL EQUIPMENT - Ravutov, Sh.T.; Uljayev, E.; Ubaydullayev, U.M. (International Journal of Psychosocial Rehabilitation, 2020)
Article is devoted to improvement of quality and the accuracy of the received results of laboratory tests of interaction process of brushes of the remover and spindles of the vertical-spindle mechanical cotton picker by use of digital equipment in replacements of the known method of an oscillography. In the work, question about influences of an elliptic trajectory of spindles in the relative movement, favorably differing from round, on qualities of cotton removal from spindles is considered. Some theoretical provisions and the received numerical results explaining features of interaction of a spindle and brush removers on round and elliptic drums are provided. The results, which is received by the offered technique using the microprocessor equipment, give the chance to evaluate efficiency of interaction of spindles and brush removers of the vertical-spindle mechanical cotton picker more objectively in the course of work. Moreover, they give chance to optimize parameters of a zone of removal of cotton from spindles which will be applied further in creation of optimum construction of newly designed harvest device.Keywords:Spindle drum, elliptic drum, spindles, remover, brush level, metal brush, contact, inductive sensors, conducting property, oscillograph, micro power supply, microprocessor, time influence, angle of influence, accuracy.Article is devoted to improvement of quality and the accuracy of the received results of laboratory tests of interaction process of brushes of the remover and spindles of the vertical-spindle mechanical cotton picker by use of digital equipment in replacements of the known method of an oscillography. In the work, question about influences of an elliptic trajectory of spindles in the relative movement, favorably differing from round, on qualities of cotton removal from spindles is considered. Some theoretical provisions and the received numerical results explaining features of interaction of a spindle and brush removers on round and elliptic drums are provided. The results, which is received by the offered technique using the microprocessor equipment, give the chance to evaluate efficiency of interaction of spindles and brush removers of the vertical-spindle mechanical cotton picker more objectively in the course of work. Moreover, they give chance to optimize parameters of a zone of removal of cotton from spindles which will be applied further in creation of optimum construction of newly designed harvest device.